Increasing Sales of MSME Products through Socialization of Digitalization Branding in Mulyorejo Village, Surabaya City - Retnaningrum, Kartika (PT Agung Media Publisher, 2024)
Digitalization of branding is one of the important efforts in improving the development of micro, small and medium enterprises (MSMEs) in the digital era. Digital branding refers to the use of digital platforms including social media websites and e- commerce to promote and build brand identity. The number of MSME players who have not implemented the concept of digitalization is one of the obstacles in business development. Socialization of digitalization branding is a strategic step to help MSME players in Mulyorejo to be able to compete in the digital economy era. The socialization with the theme Digitalization of MSME Branding was carried out with the aim of transforming conventional- based MSMEs into digital ones. Through this socialization, it is hoped that MSME players will be more familiar with the concept of the MSME Branding Digitalization system.